2017
DOI: 10.1007/s10661-017-5835-4
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal distribution of phytoplankton and its association with physico-chemical parameters in coastal waters of Malvan, west coast of India

Abstract: Malvan coast is one of the Marine Protected Area (MPA) of Maharashtra because of its rich coral reef and biodiversity. The study investigated on phytoplankton assemblage and their diversity with respect to physico-chemical parameters covering protected and unprotected area of Malvan coast. Physico-chemical parameters such as salinity, nitrite, nitrate, and ammonia did not display seasonality due to inadequate fresh water influx and allochthonous nutrient input. Positive correlation of phosphate (r = 0.96, p < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Our results were corroborated with Haridkar et al . 34 findings, where they revealed that phytoplankton species distribution in Malvan Coast with seasonal shift was influenced by their significant fluctuation in physico-chemical parameters.…”
Section: Discussionmentioning
confidence: 97%
“…Our results were corroborated with Haridkar et al . 34 findings, where they revealed that phytoplankton species distribution in Malvan Coast with seasonal shift was influenced by their significant fluctuation in physico-chemical parameters.…”
Section: Discussionmentioning
confidence: 97%
“…Generally, the mechanisms regulating the changes in phytoplankton communities are complex [44,45]. For example, the nutrient resources of aquatic ecosystems strongly affect ecosystem diversity [46]. Species are season-specific, which is a basic manifestation of phytoplankton adaptations to natural environments [10,47].…”
Section: Phytoplankton Seasonal Dynamicsmentioning
confidence: 99%
“…The most commonly applied method for the estimation of biomass is using different sizes of transect quadrate, which will calculate the amount of phytoplankton, zooplankton, plants and animals in coastal marine ecosystems (Cushing, 1958;Strickland and Parsons, 1972;McKenzie, 2003;Gross et al, 2014;Alcaraz et al, 2016;Borja et al, 2016). Diversity of coastal marine ecosystems is indicated by Pearson's correlation matrix, Shannon-Wiener diversity index and Pielou evenness (Hardikar et al, 2017). Human appropriation of net primary production (HANPP) is a useful index to estimate the human impacts on the coastal marine ecosystems, which takes the biomass index of phytoplankton, zooplankton, seagrass, fish, crabs, squids and mollusks together (Sjafrie et al, 2017).…”
Section: Rate Coastal Marine Capitalmentioning
confidence: 99%